Pengolahan Umkm Pandan Bernilai Ekonomi Tinggi Desa Wisata Cupak Jombang - Irda Agustin Kustiwi; Cholis Hidayati (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2023)
Cupak Village, Jombang is a hilly area, surrounded by forest plantations owned by Perhutani with quite good agricultural contours. The majority of the population earn their living as farmers, especially producers of tubers and other plants. Community agricultural and agricultural products have quite promising potential with the diversification and diversity of products made from raw materials into various processed foods such as porang and pandan. Cupak is a religious tourism village supported by the Ministry of Research, Technology and Higher Education's Matching Fund funding activities in 2022 by the accounting study program at 17 August University, Surabaya. Our note is that it needs to be followed up with follow-up activities in 2023, considering that there are activities that must be carried out related to food innovation made from pandan raw materials to improve the economy of the Cupak community and even tourism potential, especially religious and cultural tourism, which is held especially in the field of Green Economy. The aim of this activity is to maximize the potential for diversification and diversity of pandanus in the village. The process includes training and assistance to the community. MBKM collaboration involves Dikti personnel, DUDI, village officials and community groups who must work together in order to resolve the above problems. Implementation of the hexagonal model of local economic development which focuses on target groups, building synergy in creating the MBKM ecosystem, MSME groups and village officials, leading to achieving sustainable development.